Memory and Identity in Thanhaa Lai’s Inside Out and Back Again - Sri Saraswati (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study focuses on the memory and identity emerged in Thanhha Lai’s Inside Out and Back Again. The topic underlies memory inherited by a ten-year-old girl, Hà. Ha’s experience as a refugee from Vietnam shaped her hybrid identity later when she lives in the USA. She flees Vietnam after the fall of Saigon and resettles in Alabama. The objective of this study is to describe how memory, especially trauma and displacement, shapes Hà’s evolving identity. Using psychological approach and Postmemory theory, the study results Ha's lived and inherited experiences combine to create a hybrid identity based on cultural continuity, memory, and resiliency. The hybrid identity reflects once that the post memory creates new, blended identities from the shared experiences of past collective trauma or displacement, often in postcolonial or diasporic contexts. This study is relevant for understanding the issue of refugee and diasporic children. Children of refugee may develop hybrid identity that incorporate both their family’s past trauma and their present-day experiences in a new country, leading to cultural shifts, memory conflicts, and a new sense of self.